INTERSECTION BETWEEN LEADERSHIP STYLES AND INTENTION TO STAY: A PERSPECTIVE FROM MANUFACTURING SMES IN MALAYSIA - Dr Ahmad Fadhly Arham; Dr Rizuwan Abu Karim; Siti Nur Athirah Binti Mohd Fauzi (International Journal of Accounting, Finance and Business, 2021)
This concept paper is to investigate the relationship between transformationalleadership styles and transactional leadership styles towards employee intention to stay inmanufacturing SMEs Malaysia. Contribution of Small Medium Enterprises (SMEs) all aroundthe globe including Malaysia cannot be repudiated as this industry has contributed in GDP aswell as in job employment. However, every organization including SMEs has facing a criticalissue in which their employees keep on leaving the organization and this has turned out tocontribute to high turnover rate. In this paper, it is contended that the employee turnover ratewithin the organization is subjected to different leadership styles being practiced by the leadersof the SMEs. This research provides numerous implications. The implications for SMEsindustry are as follows. First, is to identify the best practice of leadership styles as perceivedby the employees for their organization. Second, is to identify which leadership styles betweentransformational leadership and transactional leadership that is effective to influence employeeto remain working in the organizations.